"Problematizing" carbon emissions from international aviation and the role of alternative jet fuels in meeting ICAO's mid-century aspirational goals. (August 2018) - Soria Baledón, Mónica; Kosoy, Nicolás
Abstract: Alternative jet fuels are one of the four mechanisms by the United Nations International Civil Aviation Organization (ICAO) to limit and reduce carbon emissions from international aviation. By using Carol Bacchi's what's the problem represented to be? method of discourse analysis, the objective of this paper was to identify and understand the premises and effects of the problem-solving paradigm underlying ICAO's alternative jet fuel strategy. As a result, three problem representations were identified, from which two out of four underlying assumptions have reinforced ICAO's weak sustainability approach to international aviation's growth and have led to a number of discursive, subjectification and lived effects. The selected method also allowed the authors to identify several options to disrupt those premises in favor of the implementation of more aggressive mitigation and adaptation strategies without constraining air travel demand, including: (i) raising awareness of the environmental impacts of aviation beyond the tailpipe emissions, (ii) improving the understanding of the effects of climate change on the air transport sector, and (iii) reassessing the sectoral approach to the Sustainable Development Goals so as to gain consistency with the aims of the UN 2030 Agenda for Sustainable Development .